The Role of Sex of Peers and Gender-Typed Activities in Young Children’s Peer Affiliative Networks: A Longitudinal Analysis of Selection and Influence - Martin, Carol Lynn (2012)
A stochastic actor-based model was used to investigate the origins of sex segregation by examining how similarity in sex and time spent in gender-typed activities affected affiliation network selection and how peers influenced children’s (N = 292; M age = 4.3 years) activity involvement. Gender had powerful effects on interactions through direct and indirect pathways. Children selected playmates of the same-sex and with similar levels of gender-typed activities. Selection based on gender-typed activities partially mediated selection based on sex. Children influenced one another’s engagement in gender-typed activities. When mechanisms producing sex segregation were compared, the largest contributor was selection based on sex; less was due to activity-based selection and peer influence. Implications for sex segregation and gender development are discussed.